2020
DOI: 10.3390/molecules25030439
|View full text |Cite
|
Sign up to set email alerts
|

Poly (Vinyl Butyral-Co-Vinyl Alcohol-Co-Vinyl Acetate) Coating Performance on Copper Corrosion in Saline Environment

Abstract: Poly (vinyl butyral-co-vinyl alcohol-co-vinyl acetate) named further PVBA was investigated as a protective coating for copper corrosion in 0.9% NaCl solution using electrochemical measurements such as, electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization associated with atomic force microscopy (AFM). The PVBA coating on the copper surface (Cu-PVBA) was modeled in methanol containing PVBA. Its inhibitory properties against corrosion was comparatively discussed with those of the copper s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…43 For instance, VO 2 (M) NP dispersion improved by the interaction between positively charged amine groups and negatively charged carbonyl groups in PVP was demonstrated by Kang et al. 44 Initially, we used different hydrophilic (polar) and polymers with hydrophilic and hydrophobic groups (polar and non-polar parts) such as poly ethylene glycol (PEG�a hydrophilic polymer used as a surfactant for oxide NP dispersion and capping agent 45 ), cetyltrimethylammonium bromide (CTAB�a cationic surfactant/polymer, with a long-chain molecule having a positively charged hydrophilic head and a neutral hydrophobic tail 46 ), poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate) (PVBA�having a hydrophilic vinyl alcohol group, a hydrophobic vinyl butyral group with good moisture, and corrosion-resistive properties as a protective layer and excellent adhesion on a wide range of substrates due to the presence of the vinyl acetate group 47 ), PVA, and PVP-K30 (both are hydrophilic polymers used as surfactants and/or capping agents for NP dispersion and have biocompatibility, good solubility, high melting temperature with PVA�200 °C and PVP�150 °C, optical transparency, good adhesiveness to various substrates, and excellent filmforming capability 48,49 ) to test their applicability and film performance for our desired purpose. Due to the degrading thermochromic properties of the resulting films and temperature requirement (>80 °C) during heating process of the films, we eliminated PEG and PVBA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…43 For instance, VO 2 (M) NP dispersion improved by the interaction between positively charged amine groups and negatively charged carbonyl groups in PVP was demonstrated by Kang et al. 44 Initially, we used different hydrophilic (polar) and polymers with hydrophilic and hydrophobic groups (polar and non-polar parts) such as poly ethylene glycol (PEG�a hydrophilic polymer used as a surfactant for oxide NP dispersion and capping agent 45 ), cetyltrimethylammonium bromide (CTAB�a cationic surfactant/polymer, with a long-chain molecule having a positively charged hydrophilic head and a neutral hydrophobic tail 46 ), poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate) (PVBA�having a hydrophilic vinyl alcohol group, a hydrophobic vinyl butyral group with good moisture, and corrosion-resistive properties as a protective layer and excellent adhesion on a wide range of substrates due to the presence of the vinyl acetate group 47 ), PVA, and PVP-K30 (both are hydrophilic polymers used as surfactants and/or capping agents for NP dispersion and have biocompatibility, good solubility, high melting temperature with PVA�200 °C and PVP�150 °C, optical transparency, good adhesiveness to various substrates, and excellent filmforming capability 48,49 ) to test their applicability and film performance for our desired purpose. Due to the degrading thermochromic properties of the resulting films and temperature requirement (>80 °C) during heating process of the films, we eliminated PEG and PVBA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This observation indicates the building of an oxide layer in this situation. The corroded Samide et al [114] reported the synthesis and anticorrosive coating property of Poly (vinyl butyral-co-vinyl alcohol-co-vinyl acetate) (PVBA) for copper/ 0.9% NaCl system using PDP, EIS and AFM analyses. The PVBA coating was modelled in methanol on the Cu surface.…”
Section: Polyvinyl Alcohol (Pva) As Coating Phase Corrosion Inhibitormentioning
confidence: 99%
“…Poly(vinyl butyral) is a low-cost polymer with high optical clarity, which is actually the statistical terpolymer poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate) consisted of partial hydrolysis of poly vinyl acetate [22]. It has extensive use as the interlayer in laminated safety glass, ceramic and composite fiber binders, electrode modification and anticorrosive coatings [23][24][25][26]. The hydrophobic vinyl butyral unit adds processability, elasticity, toughness and compatibility and shape-memory property while the hydrophilic vinyl alcohol and vinyl acetate moieties afford good adhesion and bonding, particularly with inorganic materials [27,28].…”
Section: Introductionmentioning
confidence: 99%